Objective measurement methods for the evaluation of socket comfort in patients with transfemoral amputation: a systematic review - Tiesler, Lisa Marie; Edel, Melanie; Wang, Fangxing; Pieroh, Philipp; Drossel, Welf-Guntram; Carabello, Alina; Zipplies, Daniel; Heyde, Christoph-Eckhard; Schleifenbaum, Stefan (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveAchieving optimal fitting for the socket-limb interface in transfemoral amputees remains a significant challenge. This iterative fitting process largely relies on subjective feedback regarding the patient’s comfort and the expertise of the prosthetist. Consequently, this review aims to explore methods for identifying issues at the socket-limb interface through both objective and subjective measurement approaches.MethodsAll articles available in MEDLINE and Web of Science up to May 2024 were screened and evaluated, with the authors conducting a quality assessment.ResultsThe socket design was the most frequently studied factor influencing the socket-limb interface (11/25), with investigations addressing challenges such as volume fluctuations (5/25), pressure and shear forces (4/25), femur pistoning (3/25), perspiration and ventilation (2/25), and prosthesis alignment (1/25). Objective measurement methods included gait analysis (6/25), mobility tests (7/25), radiological techniques (8/25), pressure sensors (5/25), and thermal sensors/imaging (2/25), as well as optical and metabolic assessments (3/25). Several studies (17/25) combined objective analyses with subjective questionnaires, such as the Socket Comfort Score (SCS) and Prosthesis Evaluation Questionnaire (PEQ), to evaluate comfort, satisfaction, and prosthetic preferences across varying socket designs. Individualized questionnaires addressing socket design preferences were also employed. Furthermore, a final clustered analysis was conducted to allow comparisons of approaches and tools used for examining similar issues. Despite methodological advancements, a lack of standardization in measurement approaches was evident.ConclusionThe findings of this systematic review highlight significant gaps in current methods for evaluating the socket-limb interface in transfemoral amputees. While both subjective questionnaires, such as the SCS and PEQ, and objective tools, including pressure sensors and motion analyses, offer valuable insights, neither approach alone is sufficient to comprehensively assess prosthetic fit and comfort. Methodological inconsistencies and the absence of standardized protocols further impede advancements in this field. This review underscores the need for a validated and standardized measurement method that combines subjective and objective approaches to enhance evaluation accuracy. Addressing these challenges will enable the development of reliable tools for assessing socket-limb interface quality, especially prosthetic fit and comfort, and drive progress in improving prosthetic functionality and patient outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023405042, identifier, CRD42023405042